Overview of the R/V Mirai Arctic Ocean cruise in 2022 - Itoh, Motoyo; Onodeara, Jonaotaro; Hatta, Mariko; Nishino, Shigeto; Fujiwara, Amane; Watanabe, Eiji; Murata, Akihiko; Kikuchi, Takashi (2022)
The 13th Symposium on Polar Science/Interdisciplinary sessions [IA] Arctic research, Thu. 17 Nov. conference object